GAMBARAN MORFOLOGI BUAH/BIJI PERUD PUSPA (BALANOPHORA FUNGOSA J.R. & G. FORST. SSP. INDICA (ARN.) B. HANSEN VAR. GLOBOSA (JUNGH.) B. HANSEN) - Sunaryo, Sunaryo (Research Center for Biology-Indonesian Institute of Sciences, 1999)
-